Off-forest tree resources of Africa: proceedings of a workshop held in Arusha, Tanzania, 1999 - Temu, A.B.; Lund, R.E.; Malimbwi, R.E.; Kowero, G.S.; Kleinn, K.; Malende, Y.; Koné, I. (African Academy of Sciences, 2000)
The workshop on ‘Off Forest Tree Resources of Africa’ was held at Arusha from 12 to 16 July 1999. It attracted 65 scientists and stakeholders from 21 counties worldwide. The workshop was sponsored by Sokoine University of Agriculture, Tanzania, the International Centre for Research in Agroforestry, the African Academy of Sciences, United States Department of Agriculture, International Union of Forest Research Organizations, the International Foundation for Science and German Technical Cooperation. The Food and Agriculture Organization of the United Nations and Global Environmental Facility were represented. Workshop participants discussed the topic under four main themes: (1) tree resources inventory and monitoring; (2) biodiversity and ecology; (3) resource management, products and services; and (4) socio economic aspects and institutional arrangements. To strengthen the discussions, participants spent one full day studying the Chagga home gardens system on the slopes of Mt. Kilimanjaro. This highly complex and mature multi strata agroforestry system demonstrates a highly intensive land use system that can be economically and ecologically sustainable. Participants made observations and recommendations on each of the themes.